Arrangements of proteins at reconstituted synaptic vesicle fusion sites depend on membrane separation - Ginger, Lucy; Malsam, Jörg; Sonnen, Andreas; Morado, Dustin; Malsam, Andrea; Söllner, Thomas; Briggs, John A. G. (FEBS letters, 2020)
Synaptic vesicle proteins, including N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs), Synaptotagmin-1 and Complexin, are responsible for controlling the synchronised fusion of synaptic vesicles with the presynaptic plasma membrane in response to elevated cytosolic calcium levels. A range of structures of SNAREs and their regulatory proteins have been elucidated, but the exact organisation of these proteins at synaptic junction membranes remains elusive. Here, we have used cryoelectron tomography to investigate the arrangement of synaptic proteins in an in vitro reconstituted fusion system. We found that the separation between vesicle and target membranes strongly correlates with the organisation of protein complexes at junctions. At larger membrane separations, protein complexes assume a ‘clustered’ distribution at the docking site, inducing a protrusion in the target membrane. As the membrane separation decreases, protein complexes become displaced radially outwards and assume a ‘ring-like’ arrangement. Our findings indicate that docked vesicles can possess a wide range of protein complex numbers and be heterogeneous in their protein arrangements.
Gesehen am 13.10.2025